THE INFLUENCE OF KNOWLEDGE LEVEL OF MOTHERS WHO HAVE BABIES AGED 6-11 MONTHS IN GROWTH SPURT ON THE FEEDING OF EARLY COMPLEMENTARY FOOD IN THE WORKING AREA OF WARUNGGUNUNG PUSKESMAS LEBAK DISTRICT 2022 - Wahyu Agustin; Mariyani Mariyani (International Journal of Medicine and Health, 2023)
Background:Breast Milk is a perfect nutrient intended for babies with complete ingredients for baby intake and has antibodies against disease prevention. Even though breastfeeding has many benefits, it turns out that the achievements of exclusive breastfeeding are still lacking. Failure to give exclusive breastfeeding is influenced by many factors, one of which is knowledge. The knowledge possessed by the mother will greatly influence the success and failure of exclusive breastfeeding. Many mothers do not know that one day the baby will experience a phase of accelerated growth from normal conditions which is called a growth spurt. At this time a mother will be worried and think that her breast milk is lacking, so she finally gives formula milk or early solids so that her baby is calm. Writing purpose:The effect of the level of knowledge of a mother who has a baby aged 6-11 months regarding growth spurt on the provision of early complementary food (MPASI) at the Warunggunung Health Center, Lebak Regency, is known in 2022. Research methods:Research method analytic observational case control design. The study sample consisted of 74 mothers with babies aged 6-11 months who were divided into a case group (mothers with babies who were given early solids) and a control group (mothers with babies who were not given early solids) with a ratio of 1:1. Sampling technique with purposive sampling. The instrument used is a questionnaire. Bivariate analysis via Chi-Square test. Research result:In the case group (babies who were given early solids) the majority or as many as 87.5% of mothers had a low level of knowledge, while in the control group (babies who were not given early solids) the majority or 78.6% of mothers had a good level of knowledge. Mothers with a good level of knowledge, only 21.4% of mothers gave Early Solids to their babies and 78.6% of mothers did not give Early Solids. Whereas in mothers with a low level of knowledge, as many as 87.5% gave Early Solids and only 12.5% ​​did not give Early Solids to their babies. There is an influence on the level of knowledge of mothers with babies aged 6-11 months about growth spurts on early complementary feeding (p value = 0.000).